Life on the edge: Tadpoles of Cycloramphidae (Amphibia; Anura), anatomy, systematics, functional morphology, and comments on the evolution of semiterrestrial tadpoles - dos Santos Dias, Pedro Henrique; Vera Candioti, Florencia; Sabbag, Ariadne Fares [UNESP]; Colaço, Gustavo; da Silva, Hélio Ricardo; Haddad, Célio F. Baptista [UNESP]; de Carvalho-e-Silva, Ana Maria Paulino Telles; Grant, Taran (Hindawi, 2021)
The evolutionary success of anurans can be partially explained by the occurrence of free-living larvae. Tadpoles occupy several distict habitats, including the terrestrial environment. Semiterrestriality appears to have evolved seven times in anurans, and tadpoles of distantly related lineages have converged in a set of phenotypic characters, such as a depressed body, ventral mouth, massive, well-keratinized and laterally compressed jaw sheaths, low fins, and well-developed hind limbs. The semiterrestrial tadpoles of the South American family Cycloramphidae remain poorly studied. In this work, we perform a comparative analysis of the external and internal morphology of these larvae, we comment on the systematic and evolutionary implications for the family, and finally, we discuss the convergent evolution of semiterrestrial tadpoles in anurans. We studied the external, buccopharyngeal, and musculoskeletal morphology of semiterrestrial tadpoles of 14 species of Cycloramphidae. These tadpoles are highly modified and present several character-states associated with semiterrestrial life. Most of them are unique and restricted to the family, such as the novel configuration of the muscles subarcualis rectus I, rectus abdominis, and levator arcuum branchialium III. We propose 13 new synapomorphies for Cycloramphidae and one for Thoropa. The presence of similar, homoplastic, character-states in all semiterrestrial tadpoles of unrelated phylogenetic lineages seems to suggest that these character-states are adaptations for semiterrestriality.
Keywords: buccopharyngeal cavity; chondrocranium; Cycloramphus; larval muscles; Thoropa